A Bayesian econometrics and risk programming approach for analysing the impact of decoupled payments in the European Union. (7th July 2021) - Basnet, Shyam Kumar; Jansson, Torbjörn; Heckelei, Thomas
Abstract : We estimate a risk‐based programming, individual farm model and apply it to study the wealth effects of crop‐related, decoupled direct payments under the European Union (EU) Common Agricultural Policy. The model expands on previous work on estimating risk‐based programming models by applying a robust Bayesian econometric framework. The results indicate that the wealth effect varies greatly between individual farms, but that its impact on aggregate crop production is small. For larger farms, in particular, removing the decoupled payments, while keeping total land constant, increases the diversity of the cropping plan.